The Role of Progressive Law and Legal Culture in Optimizing FinTech Services - Gusti Yosi Andri; Aurellia Dianti; Aris Putra Nandar; Muhammad Hanif Fatahillah; Muhammad Kalam Kahfi, (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
The lack of regulations that support technological developments in the FinTech service sector in Indonesia limits the technological innovation of industry players and the trust of service users more optimally. To analyze the regulatory and legal cultural aspects in optimizing FinTech services in Indonesia, qualitative descriptive research methods are used. The primary and secondary data that have been obtained are then analyzed through three stages, namely data reduction, data presentation, and inductive conclusion drawing. The results showed that interviews with users of fintech services revealed concerns about data security and a lack of understanding of risks, such as high interest on online loans. Industry players highlight overly rigid regulations, especially related to blockchain technology and AI, which slow down innovation and create challenges in global competition. Existing regulations, such as POJK 77/2016 and the PDP Law, are considered not comprehensive in accommodating technological developments, while regulations related to crypto assets and AI are still limited to general guidelines. Based on progressive legal theory, adaptive and responsive regulation will be able to encourage technological innovation, provide consumer protection, and accelerate the adoption of new technologies. Legal culture theory emphasizes the importance of digital literacy in increasing public trust in fintech services. The combination of these two theories provides a solid foundation for optimizing fintech services by creating an inclusive, secure, and sustainable financial ecosystem.